Fixed wage contracts and monetary non-neutrality - Maria Björklund; Mikael Carlsson; Oskar Nordström Skans (Sveriges Riksbank, 2019)
We study the importance of wage rigidities for the monetary policy transmission mechanism. Using uniquely rich micro data on Swedish wage negotiations, we isolate periods when the labor market is covered by fixed wage contracts. Importantly, negotiations are coordinated in time but their seasonal patterns are far from deterministic. Using a two-regime VAR model, we document that monetary policy shocks have a larger impact on production during fixed wage episodes as compared to the average response. The results are not driven by the periodic structure, nor the seasonality, of the renegotiation episodes.
Keywords: E23; E24; E58; J41; 330; Monetary Policy; Wages; Nominal rigidities; Micro-data